2021
DOI: 10.1029/2021ms002537
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Data‐Driven Approaches to Build Low‐Dimensional Ocean Models

Abstract: We present a comprehensive inter‐comparison of linear regression (LR), stochastic, and deep‐learning approaches for reduced‐order statistical emulation of ocean circulation. The reference data set is provided by an idealized, eddy‐resolving, double‐gyre ocean circulation model. Our goal is to conduct a systematic and comprehensive assessment and comparison of skill, cost, and complexity of statistical models from the three methodological classes. The model based on LR is considered as a baseline. Additionally,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 99 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…(2021)). One can modify the definition of the subgrid model, for example, by including memory effects, to generate a stochastic model with non‐vanishing energy input (Agarwal et al., 2021; Berner, 2005; Bhouri & Gentine, 2022; Chorin & Lu, 2015; DelSole, 2000; Gagne et al., 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021)). One can modify the definition of the subgrid model, for example, by including memory effects, to generate a stochastic model with non‐vanishing energy input (Agarwal et al., 2021; Berner, 2005; Bhouri & Gentine, 2022; Chorin & Lu, 2015; DelSole, 2000; Gagne et al., 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Wilks (2005) proposed a statistical model of stochastic residuals where free parameters were estimated from the time series of true residuals. Additional works that compare the statistical properties of stochastic 𝐴𝐴 𝐴 𝐴𝐴 and true r residuals include Shutts and Palmer (2007), Arnold et al (2013), Mana and Zanna (2014), Gagne et al (2020), Agarwal et al (2021), and Guillaumin and Zanna (2021).…”
Section: Analysis Of Stochastic Predictionsmentioning
confidence: 99%
“…It was found that both parametrizations accurately predict numerical errors and possess good uncertainty skills. The work by Agarwal et al (2021) adopts EOFs and compares several dependent stochastic models and found that models that include the dynamics and time-delay effects perform well.…”
Section: 1029/2022ms003268mentioning
confidence: 99%
“…The work by Agarwal et al. (2021) adopts EOFs and compares several dependent stochastic models and found that models that include the dynamics and time‐delay effects perform well.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if a model is only trying to represent the surface fields that are most important for the coupling to the atmosphere, the model could focus on the use of the leading principal components (if these can be derived in the presence of coastlines), and learn the interactions between the different components using data from a time-series extracted from long model (or observational) trajectories. However, a first approach towards building low-order ML models using a barotropic model showed that results from DL may not necessarily improve on more classical approaches that combine regression techniques and stochastic forcing [5].…”
Section: Timescales and Space Scalesmentioning
confidence: 99%